Development Of An Online-Based Foreign Language Test Training Application For The Academic Community - Noor, Fatwiah; Fitriah, Noor; Sholihin, Fathurrahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In the digital era, how we learn and teach has transformed, posing challenges for students and educators. This research aims to provide innovation in education by developing online application-based foreign language test training application services for the public and the academic community of UIN Antasari Banjarmasin, which is named SIYAHA. The methodology employed is research and development using the waterfall model, which involves a sequential software development process through planning, modeling, implementation (construction), and testing. The results indicate that the SIYAHA application as a foreign language test preparation application for Students was developed based on a needs analysis to accommodate user requirements through procedures including needs analysis, system design, application development, submission and evaluation, launch and implementation, and maintenance and further development. This includes a user-friendly interface designed for accessibility by students and the public, a structured question bank categorized by skill level, real-time feedback and scoring, progress tracking, and dual-language content support. The system is web-based, compatible across devices, and secure with user authentication. These features collectively support a practical, flexible, and user-centered learning experience. Additionally, The SIYAHA application meets the criteria of feasibility in terms of both application functionality and content quality.